2019
DOI: 10.1056/nejmoa1908483
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease Mortality among Former Professional Soccer Players

Abstract: BACKGROUNDNeurodegenerative disorders have been reported in elite athletes who participated in contact sports. The incidence of neurodegenerative disease among former professional soccer players has not been well characterized. METHODSWe conducted a retrospective cohort study to compare mortality from neurodegenerative disease among 7676 former professional soccer players (identified from databases of Scottish players) with that among 23,028 controls from the general population who were matched to the players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
322
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(356 citation statements)
references
References 28 publications
16
322
1
1
Order By: Relevance
“…The ongoing HEalth and Ageing Data IN the Game of football (HEADING) study52 will add important information about external and internal comparison of the association between low-impact repetitive head injury and cognitive function among British-based footballers. Recently, Scottish footballers have been shown to be at increased risk of mortality from neurodegenerative diseases, and above all dementia, compared with the general population 53…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing HEalth and Ageing Data IN the Game of football (HEADING) study52 will add important information about external and internal comparison of the association between low-impact repetitive head injury and cognitive function among British-based footballers. Recently, Scottish footballers have been shown to be at increased risk of mortality from neurodegenerative diseases, and above all dementia, compared with the general population 53…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive ongoing debate in the media as well as in the scientific literature on the potential negative effect of contact and collision sport participation on long-term neurocognitive function (Casson & Viano, 2019;Manley et al, 2017;Putukian et al, 2019). Specifically, it was suggested that the inherent exposure to (repeated) concussions or subconcussive blows may lead to an increased risk or earlier onset of neurodegenerative diseases and psychiatric disorders (Chiò, Benzi, Dossena, Mutani, & Mora, 2005;Kerr, Marshall, Harding, & Guskiewicz, 2012;Lehman, Hein, Baron, & Gersic, 2012;Mackay et al, 2019), declines in neurocognitive performance (Hume et al, 2017;Pearce, Rist, Fraser, Cohen, & Maller, 2018), and neuroimaging abnormalities (Koerte et al, 2016;Strain et al, 2015) in retired athletes. While most research on the topic has been conducted with American soccer players (Manley et al, 2017), similar findings have also been reported in rugby (Hume et al, 2017;Pearce et al, 2018), ice hockey (Tremblay et al, 2013), and soccer (soccer) (Chiò et al, 2005;Koerte et al, 2016;Mackay et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was suggested that the inherent exposure to (repeated) concussions or subconcussive blows may lead to an increased risk or earlier onset of neurodegenerative diseases and psychiatric disorders (Chiò, Benzi, Dossena, Mutani, & Mora, 2005;Kerr, Marshall, Harding, & Guskiewicz, 2012;Lehman, Hein, Baron, & Gersic, 2012;Mackay et al, 2019), declines in neurocognitive performance (Hume et al, 2017;Pearce, Rist, Fraser, Cohen, & Maller, 2018), and neuroimaging abnormalities (Koerte et al, 2016;Strain et al, 2015) in retired athletes. While most research on the topic has been conducted with American soccer players (Manley et al, 2017), similar findings have also been reported in rugby (Hume et al, 2017;Pearce et al, 2018), ice hockey (Tremblay et al, 2013), and soccer (soccer) (Chiò et al, 2005;Koerte et al, 2016;Mackay et al, 2019). However, other studies with retired contact sport athletes report no such effects related to the prevalence of neurodegenerative diseases and psychiatric disorders (Deshpande et al, 2017;McMillan et al, 2017;Vann Jones, Breakey, & Evans, 2014), neurocognitive performance (Esopenko et al, 2017;McMillan et al, 2017), or neuroimaging abnormalities (Zivadinov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of sampling also means that large scale genetic studies of microglia have not been attempted to date. Population studies have demonstrated that individuals subject to mild brain trauma are 5-fold more likely to develop Alzheimer's Disease (Mackay et al 2019). Consequently, it is of particular importance to understand the activation of human microglia in the context of acute brain injury together with the underpinning genetic contribution to neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%